Electrophysiological Characterization of Neuropathy Complicating Type 1 Diabetes Mellitus - Nimat Abuelwafaa; Hana Ahmed; Ilham Omer; Mohamed Abdullah; Ammar Ahmed; Afraa Musa (Journal of Diabetes Research, 2019)
Diabetic peripheral neuropathy (DPN) involves sensory and motor nerves, resulting in demyelination as well as axonal degeneration. This study was conducted to describe the pattern of lower limb nerve involvement in children with type 1 diabetes mellitus (DM) based on the parameters of nerve conduction study (NCS). This cross-sectional study recruited 50 children with type 1 DM having mean disease duration of 4.92±3.84 years who attended the referred clinic in Sudan Childhood Diabetes Center. Their mean age was 15.00±2.19 years, 42% were males, and 58% were females. Twenty six matched healthy control subjects were involved; their mean age was 13.88±2.46 years, 38.46% were males, and 61.54% were females. Bilateral NCS of the sensory and motor lower limb nerves was performed using Medelec Synergy machine. Interpretation of the patients’ results was based on our own control reference values. Data was analysed using IBM SPSS statistics. Out of the 50 diabetic patients, 44 (88%) had electrophysiological evidence of peripheral neuropathy (abnormalities in at least two of the electrophysiological parameters). The majority (68.2%) had motor involvement and 31.8% had sensorimotor, while none of them (0%) had pure sensory involvement. Regarding abnormal NCS parameters (conduction velocity vs. amplitude of the compound action potential), conduction slowing feature predominated in 61.4% and only few (6.8%) showed amplitude reduction, while 31.8% showed mixed features. The most frequently affected nerve was the common peroneal, followed by posterior tibial, and the least was the sural nerve. The most sensitive parameter was the common peroneal conduction velocity. Motor precedes sensory nerve involvement. The most frequent neurophysiological abnormality was the conduction slowing, and the common peroneal was the most vulnerable nerve. These findings signify generation of a protocol for early screening of neuropathy in children with type 1 diabetes.